Clinical Analysis of Pediatric Glaucoma in Central China - Liu, Qian; Liu, Changgeng; Li, Haijun; Yang, Xiaoyuan; Dong, Yangzeng; Feng, Xiaomei; Cheng, Wenjun (Frontiers in Medicine, 2022)
Purpose We aimed to describe the characteristics, epidemiology, management, and outcomes of glaucoma in pediatric patients in central China. Methods This study retrospectively analyzed inpatients with pediatric glaucoma at Henan Provincial People's Hospital, Henan Eye Institute, and Henan Eye Hospital between 2017 and 2020. Results Overall, 239 cases (276 eyes) of pediatric glaucoma in patients, comprising 87 girls (36.40%) and 152 boys (63.60%) were analyzed. The mean age was 6.65 ± 4.46, and 2.93% of the patients had a family history of glaucoma. Primary congenital glaucoma (PCG) was the most common type of glaucoma, followed by traumatic glaucoma in 8.33% of the patients, which was considered secondary glaucoma. The most common signs and symptoms were elevated intraocular pressure (IOP) and eye pain. Trabeculotomy (Trab) and microcatheter-assisted 360° trabeculotomy (MAT) combined with Trab were the most commonly performed surgeries. The IOP of patients with PCG, juvenile open-angle glaucoma (JOAG), and secondary glaucoma were 15.27 ± 7.48 mmHg, 17.16 ± 10.05, and 18.65 ± 8.55, respectively, at the final follow up. The rate of re-operations in patients with PCG, JOAG, and secondary glaucoma were 9.15%, 6.78%, and 4.69%, respectively. The mean visual acuity of the eyes with PCG, JOAG, and secondary glaucoma was 0.79 ± 0.68, 0.51 ± 0.48, and 0.53 ± 0.50, respectively. Conclusion PCG, JOAG, and traumatic glaucoma were the most prevalent subtypes in patients with pediatric glaucoma in central China. Trab and MAT combined with Trab were the most common interventions used in this study. Pediatric amblyopia might require full attention during the entire treatment, especially after glaucoma surgery. Effective preventive measures and more public education on glaucoma prevention and the importance of early diagnosis and treatment is necessary.